Neutral Mounting of Ultrahigh $Q$ Whispering Gallery Mode disc-Resonators for Metrological Applications - Yanne K. Chembo; Lukas Baumgartel; Nan Yu (IEEE Photonics Journal, 2017)
Whispering gallery mode resonators find key applications in microwave photonic oscillators for aerospace engineering, frequency synthesis, and time-frequency metrology. However, their elastic mechanical deformations induce undesirable shifts for their optical eigenfrequencies, which should ideally be immune to vibrations. We propose a mounting configuration that provides strong immunity against external vibrations and mechanical fluctuations. Numerical simulations confirm the analytical study.